2005
DOI: 10.1145/1070873.1070876
|View full text |Cite
|
Sign up to set email alerts
|

The problem of synthetically generating IP traffic matrices

Abstract: There exist a wide variety of network design problems that require a traffic matrix as input in order to carry out performance evaluation. The research community has not had at its disposal any information about how to construct realistic traffic matrices. We introduce here the two basic problems that need to be addressed to construct such matrices. The first is that of synthetically generating traffic volume levels that obey spatial and temporal patterns as observed in realistic traffic matrices. The second i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(104 citation statements)
references
References 16 publications
4
99
0
1
Order By: Relevance
“…The tail of the distribution in Figure 1a can be modeled as Pareto (the CCDF in log-log scale resembles a straight line), while the distribution in Figure 1b can be modeled as LogNormal. This confirms previous observations of the heavy-tailed nature of sourced traffic distributions [1,6,11] with a more recent dataset. On the other hand, the distribution in Figure 1c decays faster than Pareto but slower than LogNormal.…”
Section: Distribution Of Traffic Generated From Each Assupporting
confidence: 91%
See 2 more Smart Citations
“…The tail of the distribution in Figure 1a can be modeled as Pareto (the CCDF in log-log scale resembles a straight line), while the distribution in Figure 1b can be modeled as LogNormal. This confirms previous observations of the heavy-tailed nature of sourced traffic distributions [1,6,11] with a more recent dataset. On the other hand, the distribution in Figure 1c decays faster than Pareto but slower than LogNormal.…”
Section: Distribution Of Traffic Generated From Each Assupporting
confidence: 91%
“…The major reason for this, unfortunately, has been the lack of publicly available data [13] to enable such a study by the research community. An early study by Fang et al [7] showed that interdomain traffic distributions are highly non-uniform, an observation that has since been confirmed by others [1,11]. Feldmann et al [8] described a method to estimate web traffic demands using data from server logs at a large content delivery network.…”
Section: Low Effective Rankmentioning
confidence: 96%
See 1 more Smart Citation
“…Since this network is only partially instrumented with Netflow (we dispose of Netflow measurements on 34 out of 116 routers), we simulated the missing data for the sake of experiments, by following the instructions of [20]. Namely, we noticed that the fit of the partially available data with a lognormal distribution was very good, so we simulated the missing flows with respect to this distribution, and we assigned them to the non-measured OD pairs of the network thanks to a heuristic procedure based on the topology of the network [20]. The data has a resolution of 2 hours and was collected during 40 hours, and so we track the flow volumes over 20 time steps.…”
Section: Resultsmentioning
confidence: 99%
“…To capture random fluctuations in the intensity of traffic between individual SD pairs, we rely on a Gaussian model that has been shown appropriate in modeling such estimation errors [3,15]. This gives actual traffic intensities of the form r D (s, t) = r D (s, t) + N (0, εr D [s, t]) (11) r T (s, t) = r T (s, t) + N (0, εr T [s, t]) (12) where N (0, σ) denotes a normally distributed random variable with zero mean and standard deviation σ. ε controls the magnitude of possible traffic fluctuations.…”
Section: Sensitivity To Uncertain Traffic Matricesmentioning
confidence: 99%